Islamic Republic of Mauritania : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2002)
This report assesses the Observance of Standards and Codes on Fiscal Transparency for the Islamic Republic of Mauritania. During the past few years, Mauritania has made considerable efforts to improve fiscal transparency. The withdrawal of the government from commercial activities and the banking sector has helped to clarify the role of government in the economy and reduced quasi-fiscal activities. The private sector has a new investment code and is benefiting from simplification of the tax system. The legislative framework underlying the budget is also complete.